Modern Trends in Management and Marketing - Karjavovich, Karjavov Zayniddin; Musakulovna, Raxmonova Feruza; Kilichbekovich, Komilov Feruz (Research Parks Publishers, 2023)
This article highlights the role and importance of modern trends in management and marketing in enterprises. The data are compiled on the basis of author's observations and analysis of foreign literature.